Sustainable Administrative Reform Movements Policy in Joko Widodo's Administration - Yogi Suprayogi Sugandi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
Joko Widodo (Jokowi) is a leader that is widely expected to transform Indonesia into a better country. Hopes and wishes were rising when he was elected as the president of Indonesia. This paper will describe various innovations undertaken before and after his presidential inauguration as well as the assorted innovations made in reforming the administration of his cabinet. As the president of Indonesia, Joko Widodo is required to realize the aspirations of the people in freeing the government from corruption, collusion, and nepotism. The management of ministerial and non-ministerial institutions becomes the very first crucial issue undertaken by Joko Widodo. This led to a polemic in regards to reducing or increasing the number of institutions, as the Jokowi administration actually increased the amount. In Susilo Bambang Yudhoyono's administration, several policies were made systematically and based on legislations that had been approved by the lagislature. Joko Widodo's administration in more partial in nature. The administrative reform program that is highly anticipated is the continuation of the Public Service Act. This law is a step forward from the administrative reform program that aims at the creation of good governance. Changes is career path, salary system, pension and benefits for civil servants, performance-based staffing are various efforts of sustainability carried out by Joko Widodo's administration.